2017
DOI: 10.1177/1934578x1701200722
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Blood Rheology by Extract of Asana, Pterocarpus marsupium -Suppression of Platelet Aggregation Activity and Pterostilbene, as a Main Stilbene in the Extract

Abstract: The decoction from a tumbler made of heartwood of the Indian kino tree (Asana, Pterocarpus marsupium, PM) was a remedy for diabetes mellitus in Ayurveda. Diabetes mellitus is a one of the lifestyle-related diseases that finally leads to the induction of fatal diseases such as arterial sclerosis and cerebral infarction. In this study, effects on blood fluidity was investigated using extract obtained from the heartwood of PM. Oral administration of the extract reduced passage time of the blood obtained from diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In addition, a stilbene, pterostilbene, was identified as one of the active constituents. 7 Furthermore, we revealed that PM-ext had antimelanogenesis activity due to its tyrosinase inhibitory activity. Oxyresveratrol was identified as one of the active components using tyrosinase inhibitory activity-guided purification.…”
mentioning
confidence: 86%
“…In addition, a stilbene, pterostilbene, was identified as one of the active constituents. 7 Furthermore, we revealed that PM-ext had antimelanogenesis activity due to its tyrosinase inhibitory activity. Oxyresveratrol was identified as one of the active components using tyrosinase inhibitory activity-guided purification.…”
mentioning
confidence: 86%
“…D2 (309 mg) was then subjected to preparative HPLC under the following conditions: column: Waters SunFire C18 column (10 i.d. × 250 mm); mobile phase: 20% MeCN containing 0.1% formic acid; column temperature: ambient; flow rate: 5.0 mL/min; detection: UV 369 nm to obtain marsupsin (3,16.0 mg, Figure 8). The structure of 3 was elucidated by comparison of mass spectra, 1 H-and 13 C-NMR spectra, and optical rotation data with those of a previous report.…”
Section: Fractionation Of Pm-extmentioning
confidence: 99%
“…Furthermore, pterostilbene was identified as one of the active principles that inhibited platelet coagulation via cyclooxygenase inhibition. 3 Diabetes mellitus is categorized as a lifestyle-related noncommunicable disease (NCD). NCD are a group of lifestylerelated diseases, ie, cardiovascular disease, cancer, diabetes, and chronic respiratory disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 We have already reported an improvement in blood fluidity in a disseminated intravascular coagulation model by oral administration of a crude extract of P. marsupium and one of the active components was determined to be pterostilbene. 3 An improvement in blood fluidity affects blood circulation in the microsystem, and this can lighten dull facial skin. 4,5 Thus, asana may be utilized as a skin care agent and it has been used medically for serious skin diseases.…”
mentioning
confidence: 99%